Fundamental theorem of calculus under weaker forms of primitive - Lone, Nisar A.; Chishti, T. A. (Acta universitatis sapientiae. Mathematica, 2018)
In this paper we will present abstract versions of fundamental theorem of calculus (FTC) in the setting of Kurzweil - Henstock integral for functions taking values in an infinite dimensional locally convex space. The result will also be dealt with weaker forms of primitives in a widespread setting of integration theories generalising Riemann integral.